2000
DOI: 10.4049/jimmunol.165.4.2093
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways of Mannan-Binding Lectin (MBL)- and C1-Complex Autoactivation Revealed by Reconstitution of MBL with Recombinant MBL-Associated Serine Protease-2

Abstract: Mannan-binding lectin (MBL) plays a pivotal role in innate immunity by activating complement after binding carbohydrate moieties on pathogenic bacteria and viruses. Structural similarities shared by MBL and C1 complexes and by the MBL- and C1q-associated serine proteases, MBL-associated serine protease (MASP)-1 and MASP-2, and C1r and C1s, respectively, have led to the expectation that the pathways of complement activation by MBL and C1 complexes are likely to be very similar. We have expressed rMASP-2 and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(131 citation statements)
references
References 44 publications
6
118
0
4
Order By: Relevance
“…MASP-1 and MASP-2 were found to co-elute largely with the highmolecular-mass MBL (750 kDa) on Superose 6 gel filtration [46]. Further, it was reported that MBL/MASP-2 complex, which was reconstituted between MBL and recombinant MASP-2, was eluted on gel filtration chromatography at the position corresponding to the largermolecular form of MBL [47]. Consequently, we extrapolate that MASP-2 should also be eluted in the peak 1 together with MBL/MASP-1/3 complex on gel filtration chromatography.…”
Section: Discussionmentioning
confidence: 97%
“…MASP-1 and MASP-2 were found to co-elute largely with the highmolecular-mass MBL (750 kDa) on Superose 6 gel filtration [46]. Further, it was reported that MBL/MASP-2 complex, which was reconstituted between MBL and recombinant MASP-2, was eluted on gel filtration chromatography at the position corresponding to the largermolecular form of MBL [47]. Consequently, we extrapolate that MASP-2 should also be eluted in the peak 1 together with MBL/MASP-1/3 complex on gel filtration chromatography.…”
Section: Discussionmentioning
confidence: 97%
“…The MBL or any of the ficolins binds to carbohydrate structures presented by a wide range of pathogens and mediate complement activation via activation of MASP-2. MASP-2 cleaves and activates complement proteins C2 and C4, thereby generating the C3 convertase C4b2a (Vorup-Jensen et al, 2000). From this point, the complement cascade is identical to that of the classical pathway (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Binding of MBL⅐MASP complexes to sugar residues present on the cell surfaces of microorganisms results in a conformational change of MBL (15,16), which activates MASP-2. Activated MASP-2 cleaves C4 and C2 resulting in the formation of C3/C5 convertases (C4b,C2a) (17)(18)(19).…”
mentioning
confidence: 99%
“…Although activation of the lectin pathway generates C3/C5 convertases similar to those generated via the classical pathway (17), C5 activation via the lectin pathway has not been examined. The classical pathway C3/C5 convertase (C4b,C2a) is bimolecular in nature and is made up of C4b as the noncatalytic subunit and C2a as the catalytic subunit.…”
mentioning
confidence: 99%